Alternative splicing – an elegant way to diversify the function of repeat‐containing effector proteins?. Issue 2 (19th September 2016) - Betz, Ruben; Walter, Stefanie; Requena, Natalia
Abstract : This article is a commentary on Noon et al ., 212 : 444–460 .